Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/00140139.2020.1740333
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model of the effect of postural interactions on muscular activity and perceived exertion

Abstract: Musculoskeletal disorders are a prevalent disease in many Western countries. While a large number of ergonomic analyses and assessment methods are nowadays available, most current methods that assess exposure calculate overall risk scores of individual body segments without considering interaction effects of exposure variables. Therefore, a study was conducted that aimed at investigating and quantifying interaction effects of trunk inclination and arm lifting on ratings of perceived exertion (RPE) and muscle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Occupational fatigue, often caused by high job demands and long duty periods, is associated with the reduced occupational health and safety of the worker, resulting in high social and financial costs [ 1 ], and is, therefore, a major problem for modern industrial societies [ 2 , 3 , 4 ]. Following the International Standardization Organization (ISO) 6385 document (2016) pertaining to the integration of ergonomics into the designs of work systems, work-induced fatigue is characterized as a non-pathological manifestation of excessive strain, either mental, local, or general, that is entirely reversible with rest [ 5 ], and diminished human performance capabilities are attributed to the inability to effectively manage physiological stressors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occupational fatigue, often caused by high job demands and long duty periods, is associated with the reduced occupational health and safety of the worker, resulting in high social and financial costs [ 1 ], and is, therefore, a major problem for modern industrial societies [ 2 , 3 , 4 ]. Following the International Standardization Organization (ISO) 6385 document (2016) pertaining to the integration of ergonomics into the designs of work systems, work-induced fatigue is characterized as a non-pathological manifestation of excessive strain, either mental, local, or general, that is entirely reversible with rest [ 5 ], and diminished human performance capabilities are attributed to the inability to effectively manage physiological stressors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fatigue is also a problem in the context of working in a static position, like sitting for a prolonged period as in office work, and may cause a change in posture [ 11 ]. Studies have shown that unergonomic working positions correlate with increased perceived exertion [ 1 ], physical discomfort [ 12 ], and MSDs [ 13 ] that can negatively affect the work and private life quality of employees [ 14 ]. A wide body of literature describes the general causes and effects of occupational fatigue [ 4 ], while few studies have examined fatigue in the construction industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2, participants performed a twodimensional, symmetric movement in the sagittal plane with an external weight held in both hands. Since empirical evidence suggests a significant influence of trunk inclination and shoulder angle on the muscle activity of RES/LES (Hellig et al 2020), the movement was standardised accordingly. The trunk inclination was standardised to a range of 0 to 40 with the angle measured between the vertical line and the trunk longitudinal axis as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Work demands play a vital role in the development of musculoskeletal pain, often mainly due to low physical capacity and imbalances [8]. In industry, there is evidence that unergonomic working positions correlate with increased perceived exertion [9] and physical discomfort [7,10,11], which can negatively affect the work and employees' quality of life [12]. Office workers may not lift heavy weights or move in unergonomic positions, but show sedentary behaviors that correlate with lower back [13] and neck pain [14].…”
Section: Introductionmentioning
confidence: 99%